Geological characteristics of neoproterozoic motianling granitic pluton hosting uranium mineralization in North Guangxi, China: Insights from biotite chemistry - Luo, Pailong; Guo, Chunying; Pi, Qiaohui; Wang, Ning; Liu, Naiyuan (Frontiers in Earth Science, 2025)
The Motianling pluton represents a characteristic U-bearing granite pluton in South China. Biotite serves as an indicator for the mineralization of metals such as Cu, Sn, and W in granite. Previous studies have extensively investigated the U metallogenic potential of the Motianling pluton, but research on the indicative role of biotite geochemistry in U mineralization remains limited. This study selected biotite from the coarse-grained and medium-grained granites of the Motianling pluton as the research subject. Utilizing optical microscopy, electron probe microanalysis (EPMA), and other techniques, a petrographic and geochemical study was conducted, supplemented by a comprehensive analysis of the geochemical data of biotite from typical U-bearing granites in South China. The analytical results reveal that the biotite in the coarse-grained granite is Fe-biotite (FeOt: 22.88 to 26.15 wt%, Al2O3: 16.62 to 17.76 wt%, MgO: 4.52 to 6.99 wt%, TiO2: 1.37 to 3.04 wt%), while in the medium-grained granite, it is siderophyllite (FeOt: 27.96 to 30.02 wt%, Al2O3: 17.78 to 18.50 wt%, MgO: 1.41 to 2.01 wt%, TiO2: 1.43 to 2.03 wt%). Additionally, the biotite in the mediumgrained granite exhibits higher concentrations of Fe and Al but lower levels of Mg and Ti compared to the coarsegrained granite. The geochemical characteristics of biotite indicate that the Motianling granite is S-type granite, characterized by relatively low temperature and low oxygen fugacity (fO2). The geochemical properties of biotite have certain indicative significance for U enrichment. Biotite from the medium-grained granite exhibits higher U concentrations, a lower Th/U ratio, and lower crystallization temperatures and oxygen fugacity relative to the coarsegrained granite, suggesting enhanced U mineralization potential in the medium-grained granite.